Evaluation of the effects of immunization on the incidence of Covid-19 in a rural municipality of Minas Gerais (Research, Society and Development, 2023)
Faced with the tragic scenario imposed on the world by the SARS-CoV-19 virus, it was necessary to establish emergency public policies to control this pandemic. Vaccination proved to be one of the greatest recommendations for this purpose, despite having generated controversial opinions and caused revolt in part of the population. Thus, this study aims to analyze the impact of immunization against Covid-19 in a city in Minas Gerais, in order to verify that vaccines are one of the best tools for controlling viral infections. This is a field, epidemiological and descriptive study, with a quantitative approach, using data from the Municipal Health Department of Patos de Minas. The analysis of the results of the tables and graphs showed that there was a correlation between the degree of immunization and the reduction in the number of cases and deaths in this municipality, which proves that vaccination was a modifying factor in the pandemic of Covid-19.